Enhanced dimensional stability of lightweight SBR/EVA foam by an inorganic scaffold structure constructed in the cell wall. (22nd June 2022) - Ji, Zhanyou; Ma, Jianzhong; Fei, Guiqiang; Wang, Huidi; Yang, Yanlong; Ma, Zhonglei; Zhang, Guohong; Shao, Liang
Abstract: The poor dimensional stability of lightweight rubber-based foam directly restricts its application. The realization of its higher dimensional stability contributes to being widely applied in the automobile industry, military equipment, aerospace, national defense engineering, medical and health care. However, this remains a huge challenge because the crystallization of rubber is too low to counterbalance the internal stresses and strains created by the rubber chains during the foaming process. Hence, An inorganic scaffold structure, containing the organically-modified lamellar montmorillonite (KDMMT) and rod-like attapulgite (KHATP) with a carbon-carbon double bond (>CC<), has been successfully constructed in the cell wall of styrene butadiene rubber/ethylene vinyl acetate (SBR/EVA) foam, which can improve the dimensional stability of SBR/EVA foam and reduce its density. The construction of the inorganic scaffold structure ascribed to a double cross-linking network structure (-C-C- and -C-Sx -C-), which is based on the cellular heterogeneous nucleation while taking line tension effects at the melt-nucleator interface into account. The results indicate that when the density of SBR/EVA/KDMMT/KHATP composites foam with the inorganic scaffold structure was 0.24 g/cm 3, the shrinkage and post shrinkage was reduced by 56.6% and 50.6%, respectively, compared with that of SBR/EVA foam (0.28 g/cm 3 ). Meanwhile, shoe soles constructed from this material have exceptional folding resistance compared to EVA foam. Graphical abstract: The inorganic scaffold structure was constructed in the cell wall of SBR/EVA/KDMMT/KHATP foam reduced its post shrinkage by 50.6%. Image 1 Highlights: An inorganic scaffold structure was constructed by two shaped inorganic particles. This structure was constructed in the cell wall based on cell heterogeneous nucleation. The construction was ascribed to a double cross-linking network structure. The post shrinkage of SBR/EVA composite foam reduced by 50.6%. The foam with the inorganic scaffold structure has excellent folding resistance.